A cognitive definition of Neko ‘cat’ – Analysis of Japanese lexemes, phraseologisms and corpus data - Duc-Harada, Patrycja (Papers in Linguistics, 2024)
The present study attempts to define the Japanese term neko (‘cat’) in reference to the concept of the linguistic image of the world, which is based on the assumption that interpretations of reality are reflected in language. From this perspective, definitions should represent not only prototypical (objective), but also stereotypical (subjective) features of the defined mental object. To outline a cognitive definition (related also to the cognitive perspective) of neko, various aspects of the Japanese language are to be taken into consideration. Starting with lexicographic definitions, followed by a thorough analysis of lexemes, expressions, phrases and symbolisms (both onomatopoeic and echoing states) of cats’ features and bahaviours, as well as graphic representations of neko, the present research is intended to be wrapped up with a brief discussion on the possible changes occurring within the linguistic image of neko in Japan. The concluding part of the text contains a proposal of the cognitive definition of neko which reveals universal features of the linguistic image of cats as well as those specific for the Japanese perspective.